The Pandemic from COVID 19: a Lesson that we must not forget - Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2020)
This issue of the Acta Biomedica for Health Professions magazine was prepared during the lockdown, imposed by the Italian government, for the contain- ment of COVID 19. This acute syndrome was initially thought to concern only the respiratory system and for this reason it has been defined as SARS CoV-2. To date, however, we know that COVID 19 affects numerous areas of the body (1,2). In Italy, the first western country where the infection manifested itself in the form of an epidemic, we listened to health bulletins that resembled war bulletins, which reported on thousands of people affected by the virus and hundreds of dead people. [...]